2023
DOI: 10.1002/ldr.4714
|View full text |Cite
|
Sign up to set email alerts
|

Screening of new native metallophytes from copper abandoned mining site: Promising tool for phytoremediation

Abstract: A field survey on abandoned mining site ‘Bir Nehass‐Morocco’ was conducted to identify new native metallophytes as a promising tool for phytoremediation. The spatial distribution of metals in tailings and mining soils was investigated and metal accumulation in plant tissues was analyzed and compared. The results indicated that the studied area was polluted by Cu, Zn, Pb and Cd Cadmium with maximum values of 2892, 27868.3, 6982 and 63.03 mg.kg−1, respectively, which are higher than background levels for agricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…It plays a crucial role in the detoxification of cadmium in the shoots of Sedum plumbizincicola by sequestering cadmium into the vacuoles [41]. However, not all eighteen species of plants met the threshold value for copper (1000 mg/kg) and cadmium (100 mg/kg) hyperaccumulation [42,43]. For example, the concentration of cadmium in the shoot (34.2 mg/kg) of Sedum plumbizincicola in this study was significantly lower than the average value of cadmium (170-172 mg/kg) reported by Wang et al [18].…”
Section: Accumulation Of Copper and Cadmium In Plantsmentioning
confidence: 99%
“…It plays a crucial role in the detoxification of cadmium in the shoots of Sedum plumbizincicola by sequestering cadmium into the vacuoles [41]. However, not all eighteen species of plants met the threshold value for copper (1000 mg/kg) and cadmium (100 mg/kg) hyperaccumulation [42,43]. For example, the concentration of cadmium in the shoot (34.2 mg/kg) of Sedum plumbizincicola in this study was significantly lower than the average value of cadmium (170-172 mg/kg) reported by Wang et al [18].…”
Section: Accumulation Of Copper and Cadmium In Plantsmentioning
confidence: 99%